Experimental investigation of the variation of solar heat gain factors due to orientations for Elazi? province - Bektaş Ekici, Betül; Aksoy, U. Teoman (Gazi Universitesi Muhendislik-Mimarlik, 2016)
Solar radiations on the horizontal, four main vertical surfaces of a building prototype consisting of a single pane building prototype, are measured with pyranometers and recorded with a datalogger. Direct, diffuse and reflected components of the measured solar radiations were determined by using numerical correlations. The monthly average hourly Solar Heat Gain Factors (SHGF) were obtained by calculating SHGF's belonging to 343 days of the measurement period between 27 July 2010-4 July 2011. The calculations were carried out with a computer program written in MATLAB. As a result when compared with the calculated SHGF's for the measurement period ASHRAE's 40° values were found to be high with between 2.3% and nearly 90% for different directions.
Elazi? ili için güne iş isisi Kazanç faktörünün yönlere göre de?iiminin deneysel olarak incelenmesi
Keywords: Energy efficiency in buildings; Solar Heat Gain Factor; Solar radiation